Circulating Exosomal microRNA Profiles Associated with Risk of Postoperative Recurrence in Chronic Rhinosinusitis with Nasal Polyps - Chen S; Liu J; Feng Z; Zhou L; Cai Y; Jing Q (Dove Medical Press, 2024)
Siyuan Chen,1,2 Jia Liu,1,2 Zhili Feng,1,2 Liubo Zhou,1,2 Yuexiang Cai,1,2 Qiancheng Jing1,2 1Department of Otolaryngology Head and Neck Surgery, The Affiliated Changsha Central Hospital, Hengyang Medical School, University of South China, Changsha, Hunan, People's Republic of China; 2Institute of Otolaryngology Head and Neck Surgery, Hengyang Medical School, University of South China, Changsha, Hunan, People's Republic of ChinaCorrespondence: Qiancheng Jing, Department of Otolaryngology Head and Neck Surgery, The Affiliated Changsha Central Hospital, Hengyang Medical School, University of South China, Changsha, Hunan, People's Republic of China, Email 2022050001@usc.edu.cnBackground: Exosomes carry various types of transcripts and serve as promising biomarkers for inflammatory diseases. However, the role of serum exosomal microRNAs (miRNAs) in chronic rhinosinusitis with nasal polyps (CRSwNP) is poorly clarified.Methods: A prospective exploratory cohort of 10 CRSwNP patients was conducted, and the serum exosome samples were subjected to miRNA sequencing. Two independent prospective cohorts, consisting of 40 and 54 patients respectively, were recruited from different medical centers for validation. These cohorts were monitored for over two years, with postoperative recurrence serving as the primary outcome measure. The top 3 differentially exosomal miRNAs were validated in the serum samples, and their predictive values for recurrence were assessed.Results: Eight CRSwNP patients completed the follow-up, comprising 4 non-recurrent cases and 4 recurrent cases. Distinctive profiles of serum exosomal miRNAs were identified between the two groups. In the first validation cohort, reverse transcription-polymerase chain reaction results indicated elevated serum exosomal miR-3174 and miR-6750-5p expressions, along with reduced miR-192-3p levels in the recurrence group compared to the non-recurrence group. Receiver operating characteristic (ROC) curves and Kaplan-Meier survival analysis demonstrated significant correlations between expressions of exosomal miR-3174 and miR-192-3p and the risk of postoperative recurrence. These findings were further validated in the second cohort, confirming the elevation of both miRNAs in the recurrence group and their associations with recurrence risk. Additionally, serum exosomal miR-3174 levels increased in recurrent cases compared to their baseline levels.Conclusion: Circulating exosomal microRNA signatures may influence the risk of postoperative recurrence in CRSwNP patients. Serum exosomal elevated exosomal miR-3174 and decreased miR-192-3p were correlated with CRSwNP recurrence risk.Keywords: exosome, chronic rhinosinusitis with nasal polyps, biomarker, recurrence